2021
DOI: 10.1615/atomizspr.2021034553
|View full text |Cite
|
Sign up to set email alerts
|

Influence of an Oscillating Airflow on the Prefilming Airblast Atomization Process

Abstract: Thermoacoustic instabilities often occur in a combustion chamber of a jet engine when pressure fluctuations from the released heat create a closed feedback loop with the fluctuations of the inlet air velocity, causing further combustion instabilities that enhance the cycle back again. Since most jet engine combustion chambers use liquid fuel dispersed into droplets by an airblast atomizer, any fluctuations occurring in the air entering the airblast nozzle could affect the atomization process of the liquid fuel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
11
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(13 citation statements)
references
References 9 publications
2
11
0
Order By: Relevance
“…Similar behavior is observed in both Figure 4(a) and Figure 4(b) in terms of the mean velocity trend. As shown in previous studies with similar operating conditions ⁠ 8 , approximately 5 mm away from the centerline the mean droplet velocity is higher compared to the velocity at X = 0 mm; this is observed in Figure 4 as well for all four excitation frequencies examined.…”
Section: Resultssupporting
confidence: 85%
See 1 more Smart Citation
“…Similar behavior is observed in both Figure 4(a) and Figure 4(b) in terms of the mean velocity trend. As shown in previous studies with similar operating conditions ⁠ 8 , approximately 5 mm away from the centerline the mean droplet velocity is higher compared to the velocity at X = 0 mm; this is observed in Figure 4 as well for all four excitation frequencies examined.…”
Section: Resultssupporting
confidence: 85%
“…Previous studies in the test facility of the Engler-Bunte-Institute had analyzed the behavior of the spray in a single excitation frequency near 100 Hz ⁠ 7,8 . In this study, the influence of the excitation frequency and the air-to-liquid ratio (ALR), i.e.…”
Section: Introductionmentioning
confidence: 99%
“…Recent investigations suggest that the average evaporation quality is only marginally affected by acoustic excitation. However, the different inertia of droplets of different size cause a segregation of small droplets at velocity antinodes whereas bigger droplets remain unaffected by the excitation, 6,7 acting as a potential source of instability. 810 While the research on liquid combustion has mainly focused on aero engines which operate under rich non-premixed conditions, 9,11 only little research has been conducted on lean premixed liquid fuel combustion so far.…”
Section: Introductionmentioning
confidence: 99%
“…For liquid fuel combustion, additional sub-processes involving fuel atomization and evaporation may act as sources of instabilities influencing the generation of equivalence ratio waves. Recent studies indicated that even small velocity perturbations significantly affect the droplet size distribution contributing to the formation of equivalence ratio waves [16][17][18].…”
Section: Introductionmentioning
confidence: 99%